Functional analysis of a novel nonsense PPP1R12A variant in a Chinese family with infantile epilepsy - Ling Tong; Xinxin Wang; Huiqin Wang; Rong Yang; Xiaoyan Li; Xiaoguang Yin (BMC, 2024)
Abstract Background Defects in PPP1R12A can lead to genitourinary and/or brain malformation syndrome (GUBS). GUBS is primarily characterized by neurological or genitourinary system abnormalities, but a few reported cases are associated with neonatal seizures. Here, we report a case of a female newborn with neonatal seizures caused by a novel variant in PPP1R12A, aiming to enhance the clinical and variant data of genetic factors related to epilepsy in early life. Methods Whole-exome and Sanger sequencing were used for familial variant assessment, and bioinformatics was employed to annotate the variant. A structural model of the mutant protein was simulated using molecular dynamics (MD), and the free binding energy between PPP1R12A and PPP1CB was analyzed. A mutant plasmid was constructed, and mutant protein expression was analyzed using western blotting (WB), and the interaction between the mutant and PPP1CB proteins using co-immunoprecipitation (Co-IP) experiments. Results The patient experienced tonic-clonic seizures on the second day after birth. Genetic testing revealed a heterozygous variant in PPP1R12A, NM_002480.3:c.2533 C > T (p.Arg845Ter). Both parents had the wild-type gene. MD suggested that loss of the C-terminal structure in the mutant protein altered its structural stability and increased the binding energy with PPP1CB, indicating unstable protein-protein interactions. On WB, a low-molecular-weight band was observed, indicating that the protein was truncated. Co-IP indicated that the mutant protein no longer interacted with PPP1CB, indicating an effect on the structural stability of the myosin phase complex. Conclusion The PPP1R12A c.2533 C > T variant may explain the neonatal seizures in the present case. The findings of this study expand the spectrum of PPP1R12A variants and highlight the potential significance of truncated proteins in the pathogenesis of GUBS.